On the Link between Media Coverage of Anorexia and Pro-anorexic Practices on the Web - Yom-Tov, Elad; boyd, danah (International Journal of Eating Disorders, 2013)
Links between media portrayals of celebrities and participation in activities related to anorexia are of interest to both researchers and practitioners but are difficult to study over long time periods and in large populations. Here we aim to determine the links between media portrayals of celebrities and online practices related to anorexia. We examined the Internet searching activities of 9.2 million people, focusing on searches related to known celebrities, especially those perceived by the public as suffering from anorexia, and on searches indicative of anorexic practices. Additionally, we tracked media attention of individual celebrities by monitoring all messages from Twitter related to those celebrities. We found that a subset of users focus their browsing activities on celebrities perceived as anorexic. There was an increase of 14% in the hazard of performing anorexia-related searches after searching for information on the celebrities most perceived as anorexic. Media attention of a celebrity was a trigger for search activity, and when focused on a celebrity perceived as anorexic, resulted in a 33% increase in hazard for carrying out anorexic searches. Strikingly, when media attention included a reference to anorexia, the hazard decreased by 22%. Our findings suggest that it would be beneficial for media, when reporting on those celebrities who are known to suffer from anorexia, to include this information in their reporting.